2008
DOI: 10.1098/rspb.2008.0858
|View full text |Cite
|
Sign up to set email alerts
|

Autumn leaves seen through herbivore eyes

Abstract: Why leaves of some trees turn red in autumn has puzzled biologists for decades, as just before leaf fall the pigments causing red coloration are newly synthesized. One idea to explain this apparently untimely investment is that red colour signals the tree's quality to herbivorous insects, particularly aphids. However, it is unclear whether red leaves are indeed less attractive to aphids than green leaves. Because aphids lack a red photoreceptor, it was conjectured that red leaves could even be indiscernable fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
108
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(118 citation statements)
references
References 31 publications
5
108
1
Order By: Relevance
“…Interestingly, enhanced plant penetration by aphid stylets was observed on symptomatic virus-infected plants compared with healthy plants (Alvarez et al 2007). Moreover, it has long been known that aphids are significantly attracted by yellow (Doring et al 2009) and that some plant viruses induce symptoms resulting in chlorosis, mosaics or other modifications that lead to yellowing of the leaves. Aphids have been shown to prefer to land and settle on virus-infected plants with yellowing leaves, possibly owing to the fact that insect vectors use visual cues to choose suitable plants (Fereres et al 1999;Hodge & Powell 2008).…”
Section: (B) Effect Of Viral Infection On the Vectormentioning
confidence: 99%
“…Interestingly, enhanced plant penetration by aphid stylets was observed on symptomatic virus-infected plants compared with healthy plants (Alvarez et al 2007). Moreover, it has long been known that aphids are significantly attracted by yellow (Doring et al 2009) and that some plant viruses induce symptoms resulting in chlorosis, mosaics or other modifications that lead to yellowing of the leaves. Aphids have been shown to prefer to land and settle on virus-infected plants with yellowing leaves, possibly owing to the fact that insect vectors use visual cues to choose suitable plants (Fereres et al 1999;Hodge & Powell 2008).…”
Section: (B) Effect Of Viral Infection On the Vectormentioning
confidence: 99%
“…For example, Hyalopterus pruni (Geoffroy) was attracted to unsaturated tints of orange-yellow-green with an optimum at yellow, whereas Aphis fabae (Scopoli) was more attracted to saturated tints that correspond to their respective host plants Phragmites communis (Poaceae) and Beta vulgaris (Chenopo-diaceae) (Moericke 1969). Furthermore, Rhopalosiphum padi (L.) was found to be attracted to green leaves of its primary host plant in autumn instead of trees with yellow leaves as predicted by the autumn co-evolution theory and the aphid colour preference model (Archetti & Leather 2005;Döring et al 2009). These findings could be relevant for aphid control on agricultural crops.…”
Section: Introductionmentioning
confidence: 84%
“…To address this problem, Döring et al (2009) developed a colour choice model based on testing 70 different colours in the field, tentatively taking both aphid and human photoreceptor characteristics into account. The model indicated that aphids are able to distinguish between red and green leaves, with a tendency to avoid red.…”
Section: Introductionmentioning
confidence: 99%
“…This result is consistent with that obtained by Jönsson (2005), who also found that yellow is a strong visual cue for pollen beetle parasitoids. The attraction to yellow is caused by the positive input from green receptors coupled with a negative input from blue receptors in the insect eye, termed the 'green-blue colour opponent mechanism' (Döring et al 2009;Döring et al 2012). In contrast to Meligethes spp.…”
Section: Traits Affecting Parasitoid Abundance In Wfsmentioning
confidence: 99%